Personalized Secukinumab Treatment in Patients with Plaque Psoriasis Using Model-Informed Precision Dosing - Karine Rodriguez-Fernandez; Javier Zarzoso-Foj; Marina Saez-Bello; Almudena Mateu-Puchades; Antonio Martorell-Calatayud; Matilde Merino-Sanjuan; Elena Gras-Colomer; Monica Climente-Marti; Victor Mangas-Sanjuan (Pharmaceutics)
Background/Objectives: Patient care and control of inflammatory disorders, such as psoriasis, can be improved by model-informed precision dosing (MIPD) techniques based on population pharmacokinetic/pharmacodynamic (PK/PD) models. Clinical dose selection decisions based on MIPD strategies need to take account of the uncertainty associated with the individual PK/PD model parameters, which is determined by the quantity of individual observational data collected in clinical practice. Methods: The aim of this study was to propose an approach for personalized dosage regimens of secukinumab (SCK) in 22 Spanish patients with plaque psoriasis, whose severity level was considered moderate to severe, taking into account the uncertainty associated with individual parameters in a population-based PK/PD model. Results: The link between SCK serum concentrations and Psoriasis Area and Severity Index (PASI) scores was explained using an indirect response model. A maximum inhibition (Imax) drug effect model was applied to limit the progression of psoriatic skin lesions within the turnover PD mechanism, which explains the changes in PASI scores during treatment. A first-order remission rate constant for psoriatic lesions (kout = 0.11 day−1) was estimated. Conclusions: According to the MIPD strategy, 50% of patients would require an optimized regimen and 14% would require an intensified dosage regimen in comparison to current clinical treatment. This research has shown its usefulness as a tool for choosing individualized SCK dosage regimens in patients with long-lasting plaque psoriasis to improve the probability of achieving satisfactory response levels.